Classroom management practices: Indonesian secondary schools teachers’ perceptions - Yana Yopianti; Nizamuddin Sadiq (Komunitas Ilmuwan dan Profesional Muslim Indonesia (KIPMI), 2023)
The present study aims to investigate the Indonesian secondary school teachers' perspectives of practicing their classroom management to create a conducive classroom environment for learning. This research method is qualitative study, which is able to explore the perspectives of participants regarding their understanding and experience in managing classrooms to create conducive learning. The participants in this study were two teachers who taught in the urban and in rural area. After negotiating with the headmaster, the participants were recruited under a purposive sampling approach and gave their consent to participate in this study. In this study, data were collected through one-to-one interviews and analyzed using thematic analysis. Employing Garwood and Harris (2020) five parameters, two themes were resulted in each parameter. The participants were the teachers recognizing students' names and paying attention to their attitudes and intelligence. They also tried to have a good appearance, performance, and attitude as well as to make games. Regarding a consequence of breaking rules, the teacher in urban area applied academic punishments such as memorizing vocabularies; while, the one in rural area preferred to provide social punishments such as taking out the trash from classrooms. Furthermore, the teachers did not involve students in managing class rules, but made them individually or privately. Finally, both teachers informed class procedures in their teachings. The findings of this study implied that classroom management should be understood as well as practiced properly and appropriately as one of attempts the teacher could make to maintain and create a conducive learning atmosphere.